Experimental study on plantar pressure of basic step in aerobics sports - Qiu, Q.-E.; Gu, Y.-D. (Procedia Engineering, 2011)
The purpose of this study was to understand cushioning mechanical properties of the Reebok and the Huakang shoes in the basic action of aerobics sport, for evaluating the mechanical effect of those aerobics sports shoes. Though biomechanical experimental test, the plantar pressure parameters at "shoes - ground" was calculated during Opening-closing action, Suck leg beat action and playing kick beat action. From the results, all peak force, average impulse and peak pressure of the Huakang shoes was less than the Reebok shoes, but the indexes of cushion property do not exist significant differences (P>0.05).